HUBUNGAN KARAKTERISTIK, PENGETAHUAN, SIKAP DAN PENGAWASAN DENGAN KEPATUHAN PEMAKAIAN ALAT PELINDUNG DIRI PADA PETUGAS LAUNDRY (Studi di RS. X Provinsi Lampung) - Tri Puji Astuti; Ida Wahyuni; Siswi Jayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
The laundry installation is a linen washing place in hospitals that have a high risk of danger such as being electrocuted or exposed to the HIV virus. Therefore, one control effort that must be done is by using PPE. The purpose of this study was to analyze the relationship between worker behavior and compliance with the use of personal protective equipment at the laundry officer at Hospital X Lampung Province. The type of research used is quantitative by using a cross sectional study. The population in this study were all workers in the Laundry Installation. The sample used in this study were 21 people using the total sampling technique. The research instruments used were questionnaires and observation sheets. Data analysis using Rank Spearman test. The results showed that there was a significant relationship between knowledge (ρ = 0,003) and supervision (ρ = 0,001) and there was no significant relationship between age (ρ = 0,330), years of service (ρ = 0,537), education (ρ = 0,197) and attitudes (ρ = 0,375) with compliance with the use of PPE on workers in the Laundry Installation Hospital X Lampung Province. Need further research with different research variables and designs to determine other factors that influence compliance with PPE use.